Overexpression of PD‐L1 causes germ cells to slough from mouse seminiferous tubules via the PD‐L1/PD‐L1 interaction. Issue 10 (5th April 2022) - Fang, Lian; Feng, Rui; Liang, Weiye; Liu, Fang‐Fang; Bian, Gan‐lan; Yu, Caiyong; Guo, Hongmin; Cao, Yihui; Liu, Mingkai; Zuo, Jia; Peng, Yinglong; Zhao, Jie; et al.
Abstract: Spermatogenesis is a cyclical process in which different generations of spermatids undergo a series of developmental steps at a fixed time and finally produce spermatids. Here, we report that overexpression of PD‐L1 (B7 homolog1) in the testis causes sperm developmental disorders and infertility in male mice, with severe malformation and sloughing during spermatid development, characterized by disorganized and collapsed seminiferous epithelium structure. PD‐L1 needs to be simultaneously expressed on Sertoli cells and spermatogonia to cause spermatogenesis failure. After that, we excluded the influence of factors such as the PD‐L1 receptor and humoral regulation, confirming that PD‐L1 has an intrinsic function to interact with PD‐L1. Studies have shown that PD‐L1 not only serves as a ligand but also plays a receptor‐like role in signal transduction. PD‐L1 interacts with PD‐L1 to affect the adhesive function of germ cells, causing malformation and spermatid sloughing. Taken together, these results indicate that PD‐L1 can interact with PD‐L1 to cause germ cell detachment and male infertility.